2015
DOI: 10.1590/0100-69912015001005
|View full text |Cite
|
Sign up to set email alerts
|

Temporary abdominal closure with zipper-mesh device for management of intra-abdominal sepsis

Abstract: OBJECTIVE: to present our experience with scheduled reoperations in 15 patients with intra-abdominal sepsis. METHODS: we have applied a more effective technique consisting of temporary abdominal closure with a nylon mesh sheet containing a zipper. We performed reoperations in the operating room under general anesthesia at an average interval of 84 hours. The revision consisted of debridement of necrotic material and vigorous lavage of the involved peritoneal area. The mean age of patients was 38.7 years (range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 26 publications
0
6
0
1
Order By: Relevance
“…However, patients with OA do require temporary abdominal closure (TAC) to allow for a period of optimization prior to definitive closure. There are multiple techniques associated with the management of OA that can be used to facilitate TAC, such as loose packing of the abdominal cavity [1], use of towel clips [2], placement of mesh materials [3], use of polyvinyl bags [4], or even use of textile and zipper-like devices [5]. Until 2016, there was no consensus as to which treatment option was superior, although various studies indicated that negative pressure wound therapy (NPWT) and its variants were the most effective approach, yielding the best results and reducing associated complications [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, patients with OA do require temporary abdominal closure (TAC) to allow for a period of optimization prior to definitive closure. There are multiple techniques associated with the management of OA that can be used to facilitate TAC, such as loose packing of the abdominal cavity [1], use of towel clips [2], placement of mesh materials [3], use of polyvinyl bags [4], or even use of textile and zipper-like devices [5]. Until 2016, there was no consensus as to which treatment option was superior, although various studies indicated that negative pressure wound therapy (NPWT) and its variants were the most effective approach, yielding the best results and reducing associated complications [6].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with an open abdomen (OA) require temporary abdominal closure (TAC) to allow for a period of stabilization prior to definitive closure. There are multiple techniques to facilitate TAC in the management of an OA [ 1 – 5 ]. Among these techniques, negative pressure wound therapy (NPWT) is the most effective approach [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Materials such as polypropylene, polyglactin, polytetrafluoroethylene, woven polyester, polyvinylidene, among others, may be part, alone or in combination, of the composition of meshes currently used [7][8][9][10][11][12] .…”
Section: Introductionmentioning
confidence: 99%
“…Since 1981, the Department of General Surgery and Trauma Hospital of the Faculty of Medicine, Universidade de São Paulo (HCFMUSP), it was established that the open abdomen (AA) with planned reoperations would be an option for the treatment of intra-infections abdominal with systemic repercussions, whose infectious focus could not be removed in one operation 9 . In the 90's was designed the Damage Control (DC).…”
Section: Introduction Introduction Introduction Introduction Introducmentioning
confidence: 99%